The Khawarij and Their Rejection of the Sunnah - ROBI, ROBI PERMANA (Journal of Hadith Studies, 2019)
The rejection of al-Sunnah (Inkar al-Sunnah) is a movement that has been recorded in the history of the development of Hadith. One of the factors that led to the emergence of this movement was the political differences among Muslims, which caused them to split into several sects. Among these sects, those who held views different from the majority of Sunni scholars are referred to in Hadith tradition as al-mubtadi' (innovators), and the Khawarij’s views are one of the opinions among these sects. This paper aims to discuss the views of the Khawarij, who rejected the Sunnah after the Battle of Siffin, leading to the denial of the Sunnah that had been established. This article employs a literature survey method related to the subject matter discussed. One of the findings is that the Khawarij initially accepted the Sunnah of the Prophet Muhammad (PBUH) as a source of law, but after the Battle of Siffin, they rejected the Sunnah, refused arbitration (tahkim), and viewed the companions of the Prophet as unreliable (dhu'afa). They did not accept the Hadiths narrated by the companions, except for a few, with interpretations that aligned with their beliefs. This article will explain the Khawarij's response to Hadith, the aspects of Hadith they rejected, and the division of their opposition to Hadith.